(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Responding to disasters and crises is a crucial role for the government to ensure the public safety of society. Responding lies in the counter of crimes of civil or disorders, providing the urgent medical care to injured or sick people, and providing relief of natural and manmade disasters. Despite ongoing attempts to improve emergency response systems in Jeddah, Saudi Arabia, it still suffers from vulnerability. With the current development of the technology and internet of things (IoT), it became necessary to apply these techniques for improving emergency response systems in Jeddah. In this paper, we present Jeddah Smart Emergency Response System (JSERS) as a solution to improve the emergency response system in Jeddah using smart city technologiesØ² First, we discussed the problems related to the response to accidents and disasters and their history in the Kingdom of Saudi Arabia, especially Jeddah. Consequently, we described the proposed solution, followed by the architecture of the system. Following by the opportunities and the challenges of system implementation are discussed. Finally, a list of suggestions that supports this system implementation and deployment is reported.